Characterization of protein–protein interactions between the nucleocapsid protein and membrane protein of the SARS coronavirus - He, Runtao (Virus Res, 2004)
The human coronavirus, associated with severe acute respiratory syndrome (SARS-CoV), was identified and molecularly characterized in 2003. Sequence analysis of the virus indicates that there is only 20% amino acid (aa) identity with known coronaviruses. Previous studies indicate that protein–protein interactions amongst various coronavirus proteins are critical for viral assembly. Yet, little sequence homology between the newly identified SARS-CoV and those previously studied coronaviruses suggests that determination of protein–protein interaction and identification of amino acid sequences, responsible for such interaction in SARS-CoV, are necessary for the elucidation of the molecular mechanism of SARS-CoV replication and rationalization of anti-SARS therapeutic intervention. In this study, we employed mammalian two-hybrid system to investigate possible interactions between SARS-CoV nucleocapsid (N) and the membrane (M) proteins. We found that interaction of the N and M proteins takes place in vivo and identified that a stretch of amino acids (168–208) in the N protein may be critical for such protein–protein interactions. Importantly, the same region has been found to be required for multimerization of the N protein (He et al., 2004) suggesting this region may be crucial in maintaining correct conformation of the N protein for self-interaction and interaction with the M protein.